Política sexual: entre o universal e o particular, os direitos humanos LGBT em Belo Horizonte e Lisboa - Andrea Moreira Lima (2013)
The main object of this research understand and analysis the sexual policy, with emphasis on the relation between the universal and the individual aspects involved on LGBT human rights in the cities of Belo Horizonte and Lisbon. This discursion was materialized in the non-linear relations between on demands of LGBT social movements and the responses constructed by the governmental policy. It was intented to discuss some effects produced in the content of those universalist and individualist speeches about the construction of LGBT human rights policy in the reality of those two cities. Thus, the matter that permeates this study is to investigate, on relation of individual demand translation of the social movement to the universal responses constructed by governmental policies in the construction of citizenship policy and LGBT identities, focusing the cities of Belo Horizonte and Lisbon, and then which are the effects produced in the tension of the universality of human rights and the specificity of LGBT rights, recognizing that this is a political field of disputes sometimes antagonistic and of difficult consensus with the proper struggles of LGBT groups. For that matter, it was created some categories of analysis departing from the research plot, the collected data and the theoretical referential. Thus, the data were organized in more objective themes, such as, activist, governmental and mixed trajectories; international, national and municipal frameworks; conquests of the executive, legislative and judiciary powers, and the impacts in the social movement, in the public power and in the civil society, as well as, more analytical themes: Christian-naturalistic, constitutional-legislative and critical socio-historical conceptions of human rights; interface human rights and LGBT rights via regulation, emancipation, universality-equality-general, articularity-difference-specificity, relation between social movement demands and responses of public power via dialogues and consensus, conflicts and tension, resistance vs. partnership, cooptation vs. partnership. Those themes were correlated with theoretical categories, such as, translation, historicity, collective identity, social actor, universalism and particularism, human rights, sexual rights, LGBT rights among others. For that matter, we used authors of distinct traditions of thought and that, in this study, were articulated in order to construct a conceptual outline that could cover the complexity of factors related to the researched theme. It was used the following qualitative methods to collect data: semi-structured interviews, document analysis and field work. Interviews with public servants engaged in governmental offices in Belo Horizonte and Lisbon and with activists of those cities were analyzed. As a method of analysis we privileged Content Analysis and the contribution of the methodological-theoretical referential of Translation. In order to delimit an investigative field, it was demarcated at this study to the policies and actors of LGBT field of Belo Horizonte and Lisbon, as well as our own experiences of activisms, in political offices and during the carrying out of this study. As a general result, some conclusions were possibles as that the tensions produced in the relation between universalistic and particularistic perspectives in the construction of LGBT human right policies are strategic psychopolitical analyzers as a way to perceive the possible effects of enlargement, displacement and reconfiguration of universal notions of human rights front of the particularities in the struggle for LGBT rights. In an unbalanced society, it was recognized that the particularities which are universalized, most of the time, are model imposed by dominant elite. Hence, on one hand, focusing in an absolute specificity also raises some problems, such as, fragmentation and weakness of social struggles, once there is a logic of oppression that permeates most of the social minorities; on the other hand, the tensioning on specific rights enlarges, displaces and makes the notion of universality of human rights a more critical one. Consequently the relevance of a constant maintenance of conflicts and demands of LGBT groups to the enlargement of the possibilities of human rights to be universalized, guaranteeing a more pluralist and democratic character.